Survival following liver transplantation for liver‐only colorectal metastases compared with hepatocellular carcinoma. Issue 6 (13th March 2018) - Dueland, S.; Foss, A.; Solheim, J. M.; Hagness, M.; Line, P.‐D.
Abstract : Background: Liver transplantation is considered the standard of care for patients with hepatocellular carcinoma (HCC) within the Milan criteria. Liver transplantation in patients with unresectable colorectal cancer with liver‐only disease has been shown to be associated with a 5‐year overall survival rate of 56 per cent, compared with 9 per cent in patients receiving standard palliative chemotherapy. The aim of the present study was to compare disease‐free (DFS) and overall (OS) survival after liver transplantation in patients with HCC and those with colorectal metastases. Methods: Data were collected from the SEcondary CAncer (SECA) study database and an institutional (national) database of patients undergoing liver transplantation for HCC; all liver‐transplanted patients were included. Patients with colorectal metastases treated by liver transplantation were divided into high‐ and low‐risk groups for mortality based on carcinoembryonic antigen levels, response to chemotherapy, largest lesion at time of transplantation and time from primary surgery to transplantation. Results: Patients with colorectal metastases had a median of 8 lesions, compared with 1 in patients with HCC within the Milan criteria. DFS was shorter in both the high‐risk and the low‐risk colorectal cancer groups compared with that in patients with HCC. The 5‐year OS rate in the low‐risk colorectal cancer group was 75 per cent, compared with 76 per cent in patients with HCC within the Milan criteria. The 5‐year OS rate in patients with HCC beyond the Milan criteria was 56 per cent. Conclusion: The low‐risk group of patients with colorectal cancer and unresectable liver‐only disease had a 5‐year OS rate following liver transplantation similar to that of patients with HCC with lesions within the Milan criteria. Abstract : Valid treatment option